2009
DOI: 10.1287/orsc.1080.0403
|View full text |Cite
|
Sign up to set email alerts
|

Role of Domain-Specific Facets of Perceived Organizational Support During Expatriation and Implications for Performance

Abstract: In this study, we integrated social exchange theory with a spillover perspective to examine the relationships between two facets of perceived organizational support (POS) among expatriated managers (at Time 1), their work and general adjustment (at Time 2), affective commitment (at Time 2), and job performance (at Time 3). A longitudinal survey sampled 165 expatriate managers in China across three time periods. POS in the current assignment and in off-the-job life were found to interact with each other to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 56 publications
4
86
0
8
Order By: Relevance
“…Comprehensive reviews of cross-cultural organizational behavior generally pay relatively little attention to global careers beyond discussions of expatriate experiences (e.g., Gelfand et al 2007). Within the careers literature, however, considerable attention has been paid to expatriates' need to adjust to different cultures, work tasks, and interactions and the linkage of adjustment in these areas to job performance (Takeuchi et al 2009) and turnover (Stahl et al 2002). Studies have identified factors that contribute to adjustment such as support emanating from the job, supervisor, and organization as well as personal qualities such as learning orientation and selfefficacy (Bhaskar-Shrinivas et al 2005, Hechanova et al 2003, Palthe 2004.…”
Section: Global Careersmentioning
confidence: 99%
“…Comprehensive reviews of cross-cultural organizational behavior generally pay relatively little attention to global careers beyond discussions of expatriate experiences (e.g., Gelfand et al 2007). Within the careers literature, however, considerable attention has been paid to expatriates' need to adjust to different cultures, work tasks, and interactions and the linkage of adjustment in these areas to job performance (Takeuchi et al 2009) and turnover (Stahl et al 2002). Studies have identified factors that contribute to adjustment such as support emanating from the job, supervisor, and organization as well as personal qualities such as learning orientation and selfefficacy (Bhaskar-Shrinivas et al 2005, Hechanova et al 2003, Palthe 2004.…”
Section: Global Careersmentioning
confidence: 99%
“…For example, while there are certainly a few studies that have examined the consequences of adjustment, the majority of them only consider expatriates' own outcomes. Consequences that have been investigated to date include work and nonwork satisfaction (e.g., Shaffer & Harrison, 1998;Takeuchi, Yun, & Tesluk, 2002), organizational commitment (Shay & Baack, 2006;Takeuchi, Wang, Marinova, & Yao, 2009), early return intentions/withdrawal cognitions (e.g., Shaffer & Harrison, 1998;Wang & Takeuchi, 2007), and performance (Caligiuri, 1997;Kraimer et al, 2001;Kraimer & Wayne, 2004;Shay & Baack, 2006). Nonetheless, the metaanalysis conducted by Bhaskar-Shrinivas et al (2005) identified less than a dozen studies that had included consequences of adjustment.…”
Section: Implicit Assumptionsmentioning
confidence: 99%
“…Perceived organizational support can be established through SET and has been a foundational theory for IA research in the past (Shore & Coyle-Shapiro, 2003;Takeuchi, Wang, Marinova, & Yao, 2009). For example, lucrative compensation packages for high risk areas of a firm is perceived as organizational support as it indicates the organization's appreciation of the IA accepting the assignment resulting with reciprocal positive attitudes (Chenevert & Tremblay, 2009).…”
Section: Individual-level Perspectivementioning
confidence: 99%